Influence of laser scan rate on the mechanical properties of SLM TI6AL4V alloy - Matjelo, Lehlomela (Department of Mechanical Engineering, 2023)
The influence of laser scan speed on the resulting axial tensile, fracture toughness and fatigue crack growth rate (FCGR) properties has been investigated on samples produced by the selective laser melting (SLM) process from a Grade 5 Ti6Al4V metal powder; the laser scan speed was varied from 1.5 m/s to 4 m/s, while other process parameters were kept constant. Test procedures and specimens were designed in accordance with the ASTM E8/E8M, ASTM E399 and ASTM E647 standards and the corresponding microstructural characterisation carried out using optical microscopy in bright field mode. The bulk densities were investigated in line with ASTM B962-15 (Standard test method for density of compacted or sintered powder metallurgy (PM) products, using Archimedes' principle) and varied from 96% to near-100%. The ultimate tensile strength (UTS) for the as-built SLM Ti6Al4V uniaxial tensile specimens ranged from 1007 MPa to 1333 MPa, with the total elongation at failure (ductility) ranging from 4% to 9%. Nevertheless, there was generally very poor correlation between scan rate, density and measured mechanical properties. Consequently, it was proposed that the form and distribution of porosity would be more likely suited to explaining the mechanical property data. This led to a second batch of samples being produced at 3 m/s and 4 m/s for the sole purpose of investigating the influence of pores on the mechanical properties for the now stress-relieved (650°C for 4 hours in vacuum, furnace cooled) SLM Ti6Al4V samples. The uniaxial tensile test, fracture toughness test and the 3-point bend fatigue crack initiation test results were studied in conjunction with the X-ray computed tomography scans (X-ray CT scans), which were done prior to testing, and fractography carried out using the secondary scanning electron microscope (SEM) images. The UTS for the stress-relieved SLM Ti6Al4V dropped to a range of 1000 MPa – 1120 MPa, while the ductility for samples fabricated at 3 m/s was improved (7±3% to 12±2). Comparison across the 3-point bend fatigue test results for specimens fabricated at 3 m/s and 4 m/s indicated highly variable resistance to crack initiation. The results and analysis for the as-built and stress-relieved SLM Ti6Al4V mechanical test specimens led to the conclusion that the scattered mechanical measurements observed in this project could be attributed to variable porosity in samples, which overshadowed any correlation to be made between the laser scan speed and the measured mechanical properties; severe porosity in mechanical specimens played a major role in their mechanical response.